(untitled) (Journal of Parents and Teachers, 1995)
Dysphemia is a speech disorder that affects fluency and manifests itself in the repetition of syllables, especially in children aged 3 to 7 years. Its development is influenced by emotional and family factors, and early intervention is key to treatment. Therapeutic techniques adapted to each case are required to achieve effective improvement.